Evaluation of the effect of Chamomile vaginal gel on Subjective symptoms of vaginal atrophy in postmenopausal women: A randomized clinical controlled trial - Zahra Bosak; Mina Iravani; Eskandar Moghimipour; Mohammad Hossein Haghighizadeh; Parivash Jelodarian (Mashhad University of Medical Sciences, 2019)
Introduction: Vaginal atrophy is caused by estrogen deficiency in postmenopausal women and affects their quality of life. The present paper aimed to investigate the effects of chamomile vaginal gel on the subjective symptoms of vaginal atrophy in postmenopausal women. Methods: This double-blind clinical trial study was performed on 96 postmenopausal women with the subjective symptoms of vaginal atrophy in the No. 1 healthcare center in Gotvand. The subjects were randomly divided into three groups of 32 cases to receive 5% vaginal chamomile gel, conjugated vaginal estrogen cream, and placebo gel for 12 weeks. Subjective symptoms of atrophy, including irritation, itching, pain during intercourse, and vaginal dryness, were assessed using a 4-point Likert self-report questionnaire before the intervention and at 2, 6, and 12 weeks after the treatment. The data were analyzed using SPSS statistical software (version 22) and one-way analysis of variance, Kruskal-Wallis, Chi-square, and Friedman tests. P-value less than 0.05 was considered significant. Results: Subjective symptoms of vaginal atrophy improved significantly in the chamomile gel and conjugated vaginal estrogen cream treatment groups, compared with those of the placebo group (i.e., placebo vaginal gel) (P<0.001). However, there was no significant difference between the conjugated vaginal estrogen and chamomile vaginal gel groups. Conclusion: Similar to the conjugated estrogen cream, the chamomile vaginal gel mitigated the subjective symptoms of vaginal atrophy; therefore, it can be useful in women with vaginal atrophy.